The Influence of Season on the Gonad Index and Biochemical Composition of the Sea Urchin Paracentrotus lividus from the Golf of Tunis - Soumaya Arafa; Moncef Chouaibi; Saloua Sadok; Amor El Abed (The Scientific World Journal)
Seasonal variation in the gonad weight and biochemical composition of the sea urchin Paracentrotus lividus from the Golf of Tunis (Tunisia) were studied between September 2003 and August 2004. The highest gonad indices occurred in March (16.71%). The spawning period occurred between April and July and resulted in a fall in gonad indices to low level (7.12 ± 0.12%). Protein constituted the main component of the gonad, and lipid and carbohydrate were found at appreciable amounts. Consistent with the gonad cycle, sea urchin biochemical components showed clear seasonal variation with a significant decrease during the spawning period. The polyunsaturated fatty acid (PUFA) group was found at high level (40% of the total fatty acids). Of the PUFA group, eicosapentaenoic (C20:5 n−3) and eicosatetraenoic (C20:4 n−3) were the most abundant gonadal lipids. The level of PUFA was significantly affected by temperature variation showing an increase during the cold months and a decrease in the hot months.